Recent developments on fractal-based approaches to nanofluids and nanoparticle aggregation. (February 2017) - Cai, Jianchao; Hu, Xiangyun; Xiao, Boqi; Zhou, Yingfang; Wei, Wei
Highlights: Fractal properties of nanoparticle and its aggregation are introduced. Fractal-based approaches to heat transfer properties of nanofluids are analyzed. Fractal clusters and yield stress of nanoparticle aggregation are reviewed. Abstract: The properties of nanoparticles and its aggregation as well as convective heat transfer of nanofluids have received great attentions over the last few decades. It is well certified that nanoparticles and its aggregation can be successfully described by fractal theory and technology. In this review, the fractal properties of nanoparticle and its aggregation are firstly introduced, and then the recent investigations on the fractal models and fractal-based approaches that applied for effective thermal conductivity, convective heat transfer, critical heat flux and subcooled pool boiling of nanofluids, fractal clusters and yield stress property of nanoparticle aggregation are summarized.